Problem and diagnoses of Mango leaf webber infestation in Bihar - HANS, HANSRAJ; KRISHNA, BAL; KUMAR, RAKESH; Choudhary, Jaipal Singh; KUMAR, RAM; Yadav, Manish Kumar (Indian Horticulture, 2022)
Leaf webber infestation on mango trees in Bihar commences during March and continued till December with its peak activity from June to September. The leaf webber infestation reduces the potential yield of the host tree consequently, affecting the farmers' income. The article discusses the identifying features of the leaf webber and measures to control it.